the political and social contents of tolerance values in school textbooks, specifically in Sivic Education and Social science text books for the forth, fifth and sixth grades in Kurdistan Region - Ahmed, Mohamed S.; Abdullah, Bashkosh J. (Humanities Journal of University of Zakho, 2015)
This research aims to discuss the political and social contents of tolerance values in school textbooks, specifically in Sivic Education and Social science text books for the forth, fifth and sixth grades in Kurdistan Region. The research question is: what are the political and social contents of tolerance in the school textbooks for the basic education? The methodology used to answer this question is content analyses by taking single sentences, paragraphs as well as direct and indirect concepts as units of analyses.The study has a stability analysis value of 0.84, with the following findings:The value of the political contents of tolerance values in civic education textbooks for the fourth, fifth, and sixth grades is (73), whereas the value of social contents is (30).The value of the political contents of tolerance values in social science textbooks for the fourth, fifth, and sixth grades is (144), whereas the value of social contents is (24)At the end the research came out with some reconditions and suggestions.